Hardship to homeland : Pacific Northwest Volga Germans - Scheuerman, Richard D.; Trafzer, Clifford E. (Washington State University Press, 2018)
"Follows the Volga German people from Germany to Russia in the 1760s, when Catherine the Great invited colonists to settle the Volga River region. When the Russian Senate in 1871 revoked the terms of settlement, more than 100,000 Volga Germans emigrated to North and South America, many of them to the Midwest and later to the Pacific Northwest. Also includes stories based on oral histories from Volga German elders."--Provided by publisher.